HUBUNGAN FAKTOR PREDISPOSISI DAN FAKTOR PENDUKUNG TERHADAP PENCEGAHAN PENANGGANAN COVID-19 DI PUSKESMAS SABOKINGKING PALEMBANG (JURNAL SMART ANKES, 2021)
The Covid-19 pandemic that has hit Indonesia since March 2020 has caused changes in various aspects of life, especially it has a very significant influence in the aspect of public health. So, the implementation of health programs is now focused on handling Covid-19. Covid cases globally in September 2020, there were 27,288,585 cases with 887,549 deaths. The main keys to breaking the chain of spreading the virus are the use of masks, maintaining distance during social interactions, and diligently washing hands with soap and clean running water. The purpose of this study is to know the relationship between predisposing factors and supporting factors to the prevention of Covid-19 subscriptions at the Sabokingking Health Center in Palembang. The method in this research is the type of research used in this research is a quantitative description approach, on the grounds that in this study using numbers or calculations in data collection and providing an overview of the object under study through sample or population data as it is. Research design using cross sectional. The results showed that people's attitudes (p = 0.002), the role of community leaders (p = 0.001) and the role of health workers (p = 0.007). In conclusion, there is a relationship between community attitudes, the role of community leaders, and the role of health workers in preventing the handling of covid-19. It is recommended to Puskesmas which are at the forefront of implementing the government's appeal through prevention of handling covid-19, It is hoped that it can routinely and or periodically carry out health promotions, especially regarding the 2019 corona virus and can provide an example to citizens / the community in implementing prevention of handling covid.